COINTEGRATION ANALYSIS OF CRYPTOCURRENCY MARKET - TROIAN, Kyrylo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This study investigates the internal dynamics of the cryptocurrency market through a comprehensive analysis of cointegration relationships and their association with trading volumes. By examining 71,687 cryptocurrency pairs, we find that 79.06% demonstrate significant cointegration at the 95% confidence level, indicating substantial market integration within the cryptocurrency ecosystem. The analysis reveals distinct patterns of integration across different cryptocurrency categories, with NFT/Gaming, metaverse, and interoperability tokens showing particularly high levels of cointegration (>90%), while stablecoins and storage tokens exhibit relatively lower levels (
Keywords: Cryptocurrency; Market Integration; Cointegration Analysis; Trading Volume; Digital Assets; Market Structure; Portfolio Management